PEMANFAATAN AI DAN CANVA DALAM PEMBUATAN MEDIA PEMBELAJARAN KREATIF UNTUK DOSEN DAN GURU - Ritonga, Sangkot Idris; Ritonga, Mesra Wati; Sagala, Ahmad Habin; Pasaribu, Endi Zunaedy; Siregar, Jailani Syahputra; Munthe, Syafaruddin (Fakultas Ilmu Komputer, 2025)
Training on the use of AI and Canva in creating creative learning media for lecturers and teachers is a crucial skill for every lecturer and teacher. The use of technology in education is increasingly important with the development of the digital era. This research and activity aims to improve the ability of lecturers and teachers to design creative and engaging learning media through the use of artificial intelligence (AI) and the graphic design application Canva. Through a practice-based training approach, participants are equipped with the knowledge and skills to utilize various AI features in compiling materials and using Canva to design interactive and visual learning media displays. The results of the activity show an increase in participants' creativity and efficiency in creating teaching materials, as well as an increased understanding of the use of digital technology to support the learning process. This activity is expected to encourage innovation and improve the quality of teaching in higher education and school environments.